PEMUTUSAN LISTRIK SEPIHAK OLEH PT PLN BATAM DAN MEKANISME PENYELESAIAN SENGKETA KONSUMEN OLEH BPSK : Studi Putusan No. 016/PK /BPSK/X/2021 - Liska Muslimma; Diki Zukriadi (Jurnal Ilmiah Advokasi, 2026)
This research is motivated by the increasing number of disputes between consumers and public service providers, particularly regarding the unilateral action of PT PLN Batam to cut off electricity supply without following the proper Electricity Usage Control (P2TL) procedures. These actions often disregard consumers' basic rights to information and transparency, leading to harm for vulnerable consumer groups. The purpose of this research is to analyze the validity of electricity disconnection without notice and to examine the role and effectiveness of the Consumer Dispute Resolution Agency in providing legal protection and resolving disputes thru arbitration mechanisms. The research method used is normative juridical with a case study approach, a statutory approach, and a case approach. The research results indicate that the unilateral disconnection of electricity without a tiered calling procedure is an Unlawful Act because it violates the principle of decency and the legal obligations of business actors as regulated in the Consumer Protection Act and internal PLN regulations. Normatively, this research strengthens the position of the Consumer Protection Act as the legal umbrella underpinning the supremacy of consumer rights over sectoral regulations. However, systemic weaknesses were found in the Consumer Dispute Resolution Body, including a shortage of technical experts in electricity and dependence on general courts for enforcement, making the body's arbitration decisions vulnerable to legal challenges by businesses.Keywords: Arbitration; Unilateral Power Disconnection; Consumer Protection